Investigation into discontinuous low temperature waste heat utilisation from a renewable power plant in rural India for absorption refrigeration - Hamilton, Joel A.W. (2017)
This research focusses on utilising low temperature waste heat from a rural renewable power plant for absorption refrigeration. It forms part of a collaborative "Bridging the Urban Rural Divide" (BURD) research group across the United Kingdom and India investigating rural sustainable development through the provision of renewable electricity. The group is tasked with improving the educational environment and healthcare of a 45 household community (which is part of a larger village) in West Bengal, India.